Designers' guide to EN 1992-1-1 and EN 1992-1-2. Eurocode 2: design of concrete structures : general rules and rules for buildings and structural fire design - Narayanan, R. S (Designers' guides to the eurocodes, 2005)
Applies to the design of building and civil engineering structures in plain, reinforced and pre-stressed concrete. The code (for convenience referred to as EC2) is written in several parts: EN 1992 - 1 - 1; EN 1992 - 1 - 2; EN 1992 - 2; and EN 1992 - 3.